PEMAHAMAN PERAN KEPALA SEKOLAH DALAM PELAYANAN BIMBINGAN DAN KONSELING PADA MAHASISWA MANAJEMEN PENDIDIKAN ISLAM DI STAI NAHDLATUL ULAMA TASIKMALAYA - Yuyun Nuriyah Muslih; Ema Mayasari; Linda Santika (STAINU Tasikmalaya, 2022)
The purpose of this research was conducted to find out students' understanding regarding the role of the principal in guidance and counseling services in schools, so to achieve this goal a qualitative descriptive method was carried out through data collection with semi-structured interviews with 86 2nd semester students of S1 Islamic Education Management STAINU Tasikmalaya in academic 2020/2021, observation using passive participles and documentation. The results of the study stated that the experience gained by students when attending school, both from guidance and counseling services carried out in schools and from observations made independently of the performance of the principal in carrying out his duties and roles, influence the formation of students' understanding of the role of the principal in guidance and counseling services. counseling. The role school principal has a strategic position in advancing and determining the direction of the success of guidance and counseling services so that in its implementation it requires adequate skills and knowledge regarding the role and duties of the principal in guidance and counseling services as well as cooperation from various stakeholders from both government agencies and the community. Besides that, higher education institutions, especially lecturers, also have a big contribution to increasing student understanding through holding lectures in guidance and counseling courses in the Islamic education management department.